Prostate Cancer Screening Behaviors and the Related Beliefs among 50- to 70-year-old Men in Hamadan: Appraisal of Threats and Coping - Vahid Khosravi; Majid Barati; Babak Moeini; Younes Mohammadi (Hamadan University of Medical Sciences, 2018)
Background and Objective: Prostate cancer is one of the most prevalent diseases in men, and prostate cancer screening behaviors play an important role in reducing the incidence of this disease. Thus, we performed this study to investigate beliefs related to prostate cancer screening behaviors among men visiting retirement communities in Hamadan, Iran. Materials and Methods: A cross-sectional study of 403 men visiting retirement communities was performed in Hamadan, west of Iran, in 2016. The participants were selected using the multistage random sampling method. The data collection tool consisted of items on demographic characteristics and the protection motivation theory constructs. The collected data were analyzed using descriptive statistics and Pearson correlation coefficient in SPSS, version 16. Results: The mean age of the participants was 60.2±5.74 years. According to the findings, the frequency rates of performing prostate-specific antigen and digital rectal examinations were respectively 21.6% and 5.7%, showing an inappropriate condition. In addition, the level of perceived susceptibility to prostate cancer was at a low level (44.91%), but the levels of perceived response and reward efficacy were 77.88% and 75.9%, signifying a relatively desirable level. Conclusion: Based on our results, the levels of perceived susceptibility, perceived reward, fear, and perceived self-efficacy were undesirable. Thus, considering these findings in planning educational interventions seems to be necessary.